MULTI FAKTOR KUALITAS WEBSITE - Anwariningsih, Sri Huning (Gaung Informatika, 2011)
Internet technology is significant growth in the software industry. The  existence of millions of web address as one sign of the development of internet technology. Until now, the Internet is still believed to be one of the media to disseminate information. Internet more trusted by developers and users to obtain the desired information without looking at the resources. Most of the web developers pay less attention to the quality of the web. There are some developers who tend to  take  attention to the look and  less concerned with the content and vice versa.  In fact a lot of factors that must be considered when a developer will design and develop the web. A website should be consider software quality and also meet the quality  factors of  the design and  the  content.  There are  several methods used  in assessing  software quality  factors,  among which are Mc Call  and  ISO  9126. While the methods used  to measure the quality of the website and the WebQual include methods Waller. This paper aims to review what are the quality factors  that must be considered by a website designer  to design a good website based on software quality and website quality.